Natural Biphasic Calcium Phosphate Derived from Fish Bones as Biomaterial in Vital Pulp Therapy – A Literature Review - Puteri Ridha Ramadhani; Abidin, Trimurni; Farahanny, Wandania (TALENTA, 2025)
Vital pulp therapy (VPT) is performed to treat teeth affected by deep caries, trauma, or restoration-induced perforations. Synthetic bioactive materials (non-biologic materials), including Mineral Trioxide Aggregate (MTA), Biodentine, and Bioaggreates cement are commonly used in this procedure. The limitations of MTA were long setting times, difficult manipulation processes, and discoloration. Biodentine is characterized by low radiopacity, difficulty in obtaining optimal consistency, and high costs, while bioaggregate cement has an extended setting time, which can impact the success of the therapy. Therefore, this study aimed to explore the use of fishbone, an abundant biological waste and a natural biomaterial as a treatment alternative. Fishbone contains biphasic calcium phosphate (BCP), a key component in bioactive material synthesis for dentistry. The results showed that BCP had excellent properties such as calcium ions release to stimulate odontoblastic activity, osteointegrative, osteoinductive, and excellent bioactive. Additionally, the production of this material is cost-effective, safe, and less complicated. Considering these advantages, fish bone with BCP can be an excellent alternative for VPT. Keywords: Vital Pulp Therapy, Marine Fish Bone, Biphasic Calcium Phosphate